Caring for male and LGBTI sexual violence survivors: learning from local organisations - Chynoweth, S (Refugee Studies Centre, University of Oxford, 2018)
Local organisations responding to the Syrian humanitarian crisis are at the forefront of providing care for both male and LGBTI survivors of sexual violence.